Asian Monetary Integration : Will It Ever Happen? - Shanmugaratnam, Tharman (per Jacobson lecture, 2006)
This paper examines the possibility of Asian monetary integration. The paper highlights that the objectives and motivations behind the continuing debate for Asian monetary integration have now evolved. The objectives are no longer defensive, no longer preoccupied with crisis prevention or resolution. They are now more forward looking; they are about growth, about greater trade integration, about spurring greater cross-border flows of investment within Asia, and about promoting the integration and deepening of financial markets.